Research on the Teaching of Personalized Learning and Data-driven in Colleges and Universities under the Enablement of Artificial Intelligence——Taking Public English Reading Course as an Example - Feng, Jing; Zhu, Xiaolan (Journal of Research in Vocational Education, 2025)
This study focuses on the application of artificial intelligence technology in higher education, particularly its contributions to the integration and advancement of personalized learning and teaching strategies. By analyzing the empowering effects of artificial intelligence and its role in shaping personalized learning, this paper elucidates the crucial role of data-driven strategies in the teaching process. It specifically develops a case analysis within the context of public English reading classes, relying on practical operations and outcomes. The paper offers concrete insights and strategies on how to effectively integrate technological tools and data resources, as well as how to innovate teaching methods and enhance learning outcomes. Based on exploratory analysis, it summarizes the practical significance and long-term impact of using artificial intelligence to improve teaching efficiency and learning experiences.